Effects of Surface Placement of Sesbania Debris Prior to Incorporation into the Soil on Growth of Rice and Soil Properties - Pongsiri Patcharapreecha,; Duangsamorn Taja,; Hiroshi Ishida,; Hidenori Wada, (Agriculture and Natural Resources, 1993)
In a rain-fed farmer's paddy field, sesbania debris was utilized as a green manure according to the previously proposed technique, i.e. the surface placement of sesbania debris prior to incorporation into the submerged soil. The technique was confirmed to be very effective not only in avoiding the adverse effect of the applied debris which in turn enhanced growth and yield of rice but also in improving soil properties. A low input technology was suggested basing on the results of the current and the previous experiments and other available information.